Perlawanan Masyarakat Minoritas Dalam Perencanaan Pembangunan Perkotaan - Rahman Malik (SIMULACRA: JURNAL SOSIOLOGI, 2019)
The purpose of this research is to see how the resistance of minority comunities toward the silencing of their right by the government of Malang City to contribute the development planning in Malang city. According to this case it is related to public policy which is formed on the basis of collective thinking between the government and the people of Malang City as a whole. This research method is qualitative with a study approach case. The informants in this study were taken from several ranks of the community management of the Persatuan Tuna Netra Indonesia(PERTUNI) of Malang City. The data collection techniques of this study used interviews and observation. The data analysis technique used in this study is the pattern matching K.Yin. The findings of this study are related to the resistance of minority communities to the government of Malang city due to the limited rights of minorities in the planning of builders in Malang including: (1) holding a peaceful speech on the anniversary of disability. (2) carrying out advocacy efforts at the Malang City Regional Representative Council (DPRD) office. (3) Actively involved in providing education for persons with disabilities in Malang City who have difficulty accessing public facilities. (4) conducting social criticism and evaluation studies through social media related to difficult access in using public facilities for persons with disabilities.